Experimental Reactivity Descriptors of M-N-C Catalysts for the Oxygen Reduction Reaction - Zagal-Moya, J; Zagal-Moya, J; Candia-Onfray, C; Candia-Onfray, C (Elsevier Ltd, 2020)
Pyrolyzed non-precious metal catalysts (NPMCs) are promising materials to replace platinum-based catalysts in the cathode of the fuel cells. These catalysts present high catalytic activity both in alkaline and acid media for the oxygen reduction reaction (ORR). These catalysts are essentially heterogeneous as they can present different types of active sites. MNx structures have been proposed as the most active for the ORR, similar to those of the MN4 structures of metal porphyrins and phthalocyanines. Several parameters have been proposed as reactivity descriptors to correlate the structure of these materials with their catalytic activity, such as the amount of MNx and of pyridinic nitrogens in the graphitic structure. In this study, we have explored the metal center redox potential of the catalyst as an overall reactivity descriptor. We have investigated this descriptor for pyrolyzed and intact catalysts for the ORR in acid and basic media. We have found that for all catalysts tested, there is a linear correlation between the redox potential of the catalyst and the catalytic activity expressed as (log i)E). The activity increases as the redox potential becomes more positive. The correlation gives a straight line of slope close to +0.12 V/decade which agrees with the theoretical slope proposed in a previous publication assuming the adsorbed M − O2 follows a Langmuir isotherm and that the redox potential is directly linked to the M − O2 binding energy. The Tafel plots present two slopes, at low and high overpotentials. Based on these results, we proposed two different mechanisms. The low Tafel slopes of −60 mV appear at potentials where the surface concentration of M(II) active sites is potential dependent (close to the onset potential). At higher overpotentials the surface coverage of M(II) becomes constant and the slope changes to −0.120 V/decade. © 2019 Elsevier Ltd